2007
DOI: 10.1590/s1413-70542007000400021
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação microbiológica de bebidas lácteas fermentadas adquiridas no comércio varejista do sul de Minas Gerais

Abstract: RESUMOO objetivo deste trabalho foi avaliar as características microbiológicas das bebidas lácteas fermentadas comercializadas no sul de Minas Gerais. Realizou-se a enumeração coliformes totais e termotolerantes, fungos filamentosos e leveduras e bactérias lácticas. Foram coletadas amostras de cinco marcas de bebidas lácteas comercializadas em Lavras, com quatro repetições, de diferentes lotes de fabricação, para serem submetidas às análises microbiológicas. As bebidas lácteas fermentadas apresentaram-se dentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
2
2
0
9
Order By: Relevance
“…Regarding the count of coliforms, none of the samples showed typical colony formation, which results are similar to those reported by Tebaldi et al (2007) in 20 samples of fermented milks commercialized in southern Minas Gerais and by Araújo et al (2012) in passion fruitflavored sundae-type yogurt, where microbiological results for analysis of coliform bacteria showed no turbidity with acidification (turning) and gas production, indicating absence of this microorganism in the samples analyzed. Paula et al (2012) observed presence of <10 CFU ml -1 of coliforms at 30°C and 45°C in fermented milk.…”
Section: Resultssupporting
confidence: 84%
“…Regarding the count of coliforms, none of the samples showed typical colony formation, which results are similar to those reported by Tebaldi et al (2007) in 20 samples of fermented milks commercialized in southern Minas Gerais and by Araújo et al (2012) in passion fruitflavored sundae-type yogurt, where microbiological results for analysis of coliform bacteria showed no turbidity with acidification (turning) and gas production, indicating absence of this microorganism in the samples analyzed. Paula et al (2012) observed presence of <10 CFU ml -1 of coliforms at 30°C and 45°C in fermented milk.…”
Section: Resultssupporting
confidence: 84%
“…A presença de coliformes em iogurtes é limitada pelos valores de pH, logo sua ausência na maioria das amostras coletadas é um resultado que tem sido encontrado por outros autores tanto para iogurte como para bebidas lácteas (HOFFMANN et al, 1997;LIMA et al, 2009;TEBALDI et al, 2007). A ausência de coliformes nas amostras avaliadas pode ser indicativa de boas condições higiênico-sanitárias durante o processo de elaboração dos produtos (LIMA et al, 2009).…”
Section: Tabela 2 -Análises Microbiológicas Das Sete Amostras De Ioguunclassified
“…As amostras foram diluídas decimalmente em água peptonada 0,1 % (m/v) e uma alíquota de 1 mL de cada diluição foi distribuída em placas de petri e homogeneizada no meio de cultura ágar MRS (Himédia ® ). As placas foram incubadas a 37 °C /72 h (Tebaldi et al, 2007).…”
Section: Metodologia Analíticaunclassified